Fred D. Guker, Revised Ordinances of the City of Red Bud, Illinois 35 (1898) - (:unkn) unknown (My University, 1898)
35. Article 3-Public Safety, §8-Selling Weapons to Minors. Passed March 1, 1898, & Published March 29, 1898: Prohibited selling, giving, loaning, hiring, bartering, any minor a revolver, gun, derringer, slung shot, cross knuckles, knuckles of lead, brass, or other metal, Bowie-knife, dirk, dagger, or any other dangerous or deadly weapon. Violators guilty of a misdemeanor.
Keywords: TRANSFER - MINORS